Desverticalização das cadeias produtivas no setor de produção de biomedicamentos e a utilização das empresas CMOs (Contract Manufacturing Organization) - Silva, Felipe Rodrigues da (2016)
The decision between doing internally or outsource an activity is considered strategic to an organization. The purpose of this work was to study the current situation of the biopharmaceutical industry, seeking to understand how, why and where the organizations of the area are choosing to outsource their production activities. Considering a recent tendency to the movement, several companies (called CMOs) are specializing in providing production services. The research used as main sources of information literary references and insights obtained from interviewed experts in the area. The occurrence of the movement was confirmed in biopharmaceutical companies, mainly influenced by issues of cost, focus in core activities, operational flexibility and long-term strategies. The steps of scale up/ batches production for phase III clinical trials were identified as the most frequently outsourced, followed closely by the final processing and, finally, the complex activities for API manufacturing. The study demonstrated the need of robust systematic processes for the selection of CMOs companies and emphasized the importance of transparency in outsourcing contracts. It also evaluates the interference of circumstances related to the complexity of biological processes, company size, geographic location and the influence of intellectual property issues. At the end, there is a brief survey of the main CMOs companies providing services in this area around the world. It was possible to conclude that the decision to outsource productive activities in biopharmaceutical companies should be carefully evaluated and depends on the analysis of all the circumstances addressed in this work.